2021
DOI: 10.26434/chemrxiv-2021-x05x1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical Regeneration of Anthraquinones for Lifetime Extension in Flow Batteries

Abstract: Aqueous organic redox flow batteries (AORFBs) offer a safe and potentially inexpensive solution to the problem of storing massive amounts of electricity produced from intermittent renewables. However, molecular decomposition is the major barrier preventing AORFBs from being commercialized. Structural modifications can improve molecular stability at the expense of increased synthetic cost and molecular weight. Utilizing 2,6-dihydroxy-anthraquinone (DHAQ), without further structural modification, we demonstrate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…This led us to think that the observed capacity fading was not only a calendar phenomenon but was also correlated to the duration of the CV step at 1.3 V performed at the end of each charge, which increased along with the current density. This result tends to show that the 2,3-DHAQ degradation kinetic increases as it is longer subjected to more negative potential, as previously observed [59].…”
Section: Long Term Cycling Evaluation Of 3000 Cyclessupporting
confidence: 86%
See 1 more Smart Citation
“…This led us to think that the observed capacity fading was not only a calendar phenomenon but was also correlated to the duration of the CV step at 1.3 V performed at the end of each charge, which increased along with the current density. This result tends to show that the 2,3-DHAQ degradation kinetic increases as it is longer subjected to more negative potential, as previously observed [59].…”
Section: Long Term Cycling Evaluation Of 3000 Cyclessupporting
confidence: 86%
“…However, the oxidation performed during the deep discharge induced the recovery of the initial 2,3-DHAQ compound and of its corresponding capacity. This hypothesis was recently confirmed by the work of Jing et al [59].…”
Section: Long Term Cycling Evaluation Of 3000 Cyclessupporting
confidence: 59%
“…To further confirm the formation of anthrone derivatives, we chemically synthesized diethylsulfonated-2,6-anthrone (anthranol) (ADES) and found that its 1 H NMR chemical shifts and peak splitting are indeed in line with those in the cycled and thermally treated AQDES spectra (Figure d). We previously found that anthrone derivatives can be chemically oxidized to AQs when exposed to air or other oxidants ,, and electrochemically oxidized back to AQs when proper potentials are applied . We built an electrochemical cell of 5 mL of 0.05 M ADES paired with 15 mL of 0.1 M AQDS (anthraquinone-2,7-disulfonate) in 1 M H 2 SO 4 for ADES electrochemical oxidation.…”
mentioning
confidence: 99%
“…Ultimately, this provides opportunities for molecular engineering to minimize reactions that are detrimental to battery performance, or even suggest ways to revert decomposition and rejuvenate the electrolyte. [23] In this contribution, we present a detailed study of the molecular stability of bipolar Kuhn-type verdazyls in the context of symmetrical RFBs based on these materials. The structure and reactivity of radical 1 (Scheme 1) across the three relevant states-of-charge is reported, which provides key chemical insight into the factors that contribute to molecular decomposition and thus battery capacity fade.…”
Section: Introductionmentioning
confidence: 99%